'Reflex' HPLC testing as a screening modality for variant hemoglobins: A pilot study of 1310 cases at a pediatric referral hospital. Issue 5 (July 2014) - Verma, Sarika; Talukdar, Bibek; Gupta, Ruchika
<x content-type="archive" xml:space="preserve">Abstract</x> Objective High-performance liquid chromatography (HPLC) has been evaluated as useful technique for detection of variant hemoglobins in newborn screening, ethnicity-based screening, and patients with abnormal hemoglobin electrophoresis. This study aimed at evaluating this technique as 'reflex' testing in a pediatric referral center. Methods This study included 1317 children visiting the pediatric hospital, who underwent HPLC analysis on anticoagulated blood samples. These patients were divided into clinician-requisitioned HPLC (group A), 'reflex' testing for anemia (group B), and unrelated etiologies (group C). HPLC graphs were evaluated for various hemoglobins. Statistical analysis was performed for comparison between these groups for frequency of abnormal HPLC assay and various red cell parameters. Results The frequency of abnormal HPLC assay was 22.89% in group A (125 of 546 cases), 26.89% in group B (78 of 290 cases), and 31.8% in group C (153 of 781 cases) with statistically significant difference. The most frequent variant in all three groups was thalassemia trait. Thalassemia intermedia and major, both were detected in few patients in groups B and C. Conclusion 'Reflex' testing for hemoglobin variants can be undertaken for pediatric samples to enhance detection of these variants and avoid an additional venepuncture.